A method for preparing a rust-converting, water-resistant coating

CN116516333BActive Publication Date: 2026-10-27TAISHAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310454978.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-25
Publication Date
2026-10-27
Estimated Expiration
2043-04-25

AI Technical Summary

Technical Problem

磷酸型铁锈转化剂耐水性较差,而亚铁氰化钾与铁锈作用后可生成蓝色的亚铁氰酸盐(即普鲁士蓝),但直接使用效果很差,一般只能用于喷砂后对局部未除尽的残锈作辅助处理

Benefits of technology

[0021](1)本发明利用单宁酸与金属离子的配位络合作用,使用时无需预先除锈,将铁锈转化为一层保护性的膜层,使复杂的锈层成分转变为稳定的产物,并使之在海洋环境中较长时间内不会返锈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116516333B_ABST
    Figure CN116516333B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a rust conversion waterproof coating, and comprises the following steps: (1) adding tannic acid into water to obtain a tannic acid aqueous solution; (2) adding stearic acid into anhydrous ethanol to obtain a modifier; (3) immersing a rust sample into the tannic acid aqueous solution, then taking out and cleaning, and then blowing dry with cold air; (4) adjusting the pH value of the tannic acid aqueous solution to about 8, then immersing the rust sample into the tannic acid aqueous solution, taking out and drying after the immersion; (5) immersing the rust sample into an AgNO3 solution to obtain a rust conversion sample; and (6) placing the rust conversion sample into the modifier to react, taking out after the reaction, and naturally drying in air to obtain a modified super-hydrophobic rust conversion sample. The super-hydrophobic coating prepared by the method has uniform roughness, excellent hydrophobicity, good self-cleaning performance and mechanical performance, and high stability, can effectively resist the entry of corrosive ions in a marine environment, and greatly enhances the corrosion resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rust conversion coating preparation, and more specifically to a method for preparing a rust conversion waterproof coating. Background Technology

[0002] Under the corrosive conditions of the marine environment, the original coating is prone to peeling off, exposing the substrate. In complex environments, exposed steel surfaces are easily corroded. The damage caused by steel corrosion can range from material and facility failure to catastrophic accidents, even threatening the safety of facilities and personnel. Therefore, corrosion prevention of marine engineering structures has become one of the critical issues that cannot be ignored today.

[0003] The most convenient and economical method for corrosion protection of steel substrates in marine environments is coating protection. However, the effective service life of the coating depends on good surface preparation to fully realize its anti-corrosion performance. However, due to environmental and conditional limitations, it is often difficult to perform thorough surface treatment according to rust removal standards for existing rusted steel surfaces. The treated substrate usually still contains varying degrees of rust and is frequently exposed to the highly humid and corrosive environment of the ocean. Directly applying ordinary coatings to such substrates often fails to achieve the desired anti-corrosion effect. Therefore, there is an urgent need for an effective surface coating that can be applied to rust-containing surfaces.

[0004] Rust conversion agents can transform rust into a protective film, offering a more convenient and effective alternative to traditional methods. Currently, the main rust conversion agents include phosphoric acid and potassium ferrocyanide. Phosphoric acid-based rust conversion agents have poor water resistance, while potassium ferrocyanide reacts with rust to form blue ferrocyanide (Prussian blue), but its direct application is ineffective and is generally only used as an adjunct treatment for residual rust after sandblasting. Furthermore, these phosphorus- and potassium cyanide-containing materials pollute the environment; therefore, while focusing on improving corrosion resistance, the environmental friendliness of conversion materials must be given greater attention. Summary of the Invention

[0005] Based on the above-mentioned technical problems, the present invention proposes a method for preparing a rust-converting waterproof coating.

[0006] The technical solution adopted in this invention is:

[0007] A method for preparing a rust-converting waterproof coating includes the following steps:

[0008] (1) Add tannic acid to water and stir to dissolve it to obtain an aqueous solution of tannic acid;

[0009] (2) Stearic acid was added to anhydrous ethanol and stirred to dissolve, thus obtaining the modifier;

[0010] (3) Soak the rusted sample in tannic acid aqueous solution for the first time. After soaking, take it out, wash it with water, and dry it with cold air.

[0011] (4) Adjust the pH value of the tannic acid aqueous solution with NaOH solution, and then soak the rusted sample treated in step (3) in the tannic acid aqueous solution after adjusting the pH value for the second time. After soaking, take it out, wash it with water, and dry it in a constant temperature oven.

[0012] (5) Immerse the rusted sample treated in step (4) in AgNO3 solution. After immersion, take it out, rinse it with water, and dry it in a constant temperature oven to obtain the rust-converted sample.

[0013] (6) Place the rust conversion sample treated in step (5) into the modifier prepared in step (2) for reaction. After the reaction is completed, take it out and let it air dry naturally to obtain the modified superhydrophobic rust conversion sample.

[0014] Preferably, in step (1): the stirring time is controlled to be 15-20 min; the concentration of the tannic acid aqueous solution is 2-4 mg / ml.

[0015] Preferably, in step (2): the mass ratio of stearic acid to anhydrous ethanol is 1:40-60; a magnetic stirrer is used for stirring, the stirring speed is controlled at 500-600 r / min, the stirring temperature is 60-65℃, and the stirring time is 10-15 min.

[0016] Preferably, in step (3): the sample is stirred during soaking so that the rusty sample is in a suspended state in the tannic acid aqueous solution; the first soaking time is controlled to be 2-3 hours.

[0017] Preferably, in step (4): the concentration of the NaOH solution is 1-1.2 mol / L, the pH value of the tannic acid aqueous solution is adjusted to 8-8.5 using NaOH solution; the second soaking time is controlled to be 1-3 min; and the drying temperature of the constant temperature box is controlled to be 60-70℃.

[0018] Preferably, in step (5): the concentration of the AgNO3 solution is 2-3 mg / ml; the soaking time is controlled to be 2-3 h; and the drying temperature of the constant temperature box is 60-70 ℃.

[0019] Preferably, in step (6), the reaction time is 1-2 hours.

[0020] The beneficial technical effects of this invention are:

[0021] (1) This invention utilizes the coordination complexation of tannic acid and metal ions, eliminating the need for pre-rust removal during use. It transforms rust into a protective film, converting complex rust components into stable products, and preventing rust recurrence in marine environments for extended periods.

[0022] (2) The present invention obtains a superhydrophobic coating by further constructing a good micro / nano hierarchical structure and using hard acid for modification reaction; the superhydrophobic coating has uniform roughness, excellent hydrophobicity, good self-cleaning performance and mechanical properties, high stability, and can effectively resist the entry of corrosive ions in the marine environment, greatly enhancing the corrosion resistance of the coating.

[0023] (3) The raw materials such as tannic acid used in this invention are green and environmentally friendly. No volatile solvents are used in the preparation process, no heating treatment is required, and they will not cause pollution or harm to the environment and human body. This is conducive to large-scale industrial use. Attached Figure Description

[0024] Figure 1 This is a process flow diagram of the method for preparing the rust-converting waterproof coating of the present invention;

[0025] Figure 2 This is a schematic diagram illustrating the principle of preparing a superhydrophobic rust-converting coating according to the present invention.

[0026] Figure 3 This is a surface morphology image of the rusted steel sheet before treatment in Embodiment 1 of the present invention;

[0027] Figure 4 This is a surface morphology image of the superhydrophobic rust-converting steel sheet prepared in Example 1 of the present invention;

[0028] Figure 5 This is a test diagram of the surface water contact angle of the rusted steel sheet before treatment in Embodiment 1 of the present invention;

[0029] Figure 6 This is a test image of the surface water contact angle of the superhydrophobic rust-converting steel sheet prepared in Example 1 of the present invention;

[0030] Figure 7 The Fourier transform infrared spectra of the rusted steel sheet and the rust-converted steel sheet before treatment in Embodiment 1 of the present invention are shown.

[0031] Figure 8 This is a graph showing the surface wear test data of the superhydrophobic rust-converting steel sheet prepared in Example 1 of the present invention. Detailed Implementation

[0032] The existing methods for preparing rust-converting coatings have the following disadvantages: (1) The substrate must be ground and rust-removed before preparation, and then the rust-containing coating is brushed onto the rusted steel surface. The workload is large and it is not suitable for large-scale processing. (2) Rust-converting agents containing phosphorus and potassium cyanide are required, or zinc phosphate, acrylic emulsion and / or activator sodium dodecylbenzene sulfonate are required. All of the above materials are irritants, which are harmful to the environment and have an adverse effect on aquatic organisms. (3) The rust-converting coatings prepared by the existing methods have insufficient water resistance and limited service life. (4) The existing methods are complicated to prepare, have long reaction time, and often require high temperature treatment, which is dangerous and not conducive to on-site implementation.

[0033] Based on the above-mentioned technical problems, this invention proposes a method for preparing a rust-converting waterproof coating. This method does not require pre-rust removal, but rather treats the rust-bearing layer to transform it into a protective film layer, converting the complex rust layer components into stable products. This achieves the goal of directly covering the surface without rust removal. Furthermore, stearic acid is used as a hydrophobic modifier to superhydrophobically modify the converted film layer, resulting in a rust-converting waterproof coating that will not rust again for a long time in a marine environment.

[0034] The tannic acid used in this invention is a polyphenolic compound widely found in plants, a natural organic substance, and harmless to the environment. When tannic acid reacts with rust, it forms an iron tannate complex, which adheres well to the steel surface, transforming the rust layer into a complex for protection. However, in long-term marine environments, the water resistance of the complex conversion layer is insufficient, resulting in a limited lifespan. Furthermore, this invention uses silver nitrate solution to construct a good micro / nano-level structure and employs stearic acid for hydrophobic modification. The stearic acid molecule contains long-chain alkyl and carboxyl groups; its alkyl portion exhibits significant hydrophobic properties, forming a hydrophobic protective layer or shell on the surface of an object, thus achieving surface modification through physical adsorption. In addition, the carboxyl functional group of stearic acid itself possesses various reactivity. The hydrophobic groups (-CH2 and -CH3) in stearic acid are grafted onto the material surface, thereby achieving hydrophobicity in the steel sheet. The steel sheet surface has a large number of -OH groups, which combine with the -COOH at the end of the stearic acid through esterification. Stearic acid undergoes esterification, thereby reducing the surface energy of the material to achieve superhydrophobicity. Furthermore, the nonionic nature of stearic acid indicates that it will not cause electrochemical reactions or adversely affect the matrix.

[0035] This invention discloses a method for preparing a rust-converting waterproof coating. During use, no pre-rust removal is required; instead, the rust is directly converted into a protective coating, transforming the complex rust composition into a stable product. The rust-converting coating prepared by this invention exhibits strong water resistance, good corrosion resistance, and excellent self-cleaning and mechanical properties. This invention requires no heating treatment, is easy to apply, and is an environmentally friendly surface treatment technology for rusted steel, reducing environmental pollution and facilitating large-scale industrial application. The tannic acid and stearic acid used in this invention are non-toxic and environmentally friendly.

[0036] The present invention will be further described below with reference to specific embodiments.

[0037] Example 1

[0038] like Figure 1 As shown, a method for preparing a rust-converting waterproof coating includes the following steps:

[0039] (1) Add 3g of tannic acid (TA) to 1000ml of water and stir with a glass rod for 15min to completely dissolve it, so as to obtain an aqueous solution of tannic acid with a concentration of 3mg / ml.

[0040] (2) Stearic acid (SA) is added to anhydrous ethanol at a mass ratio of 1:50. Stir with a magnetic stirrer at 60°C and 600r / min for 10 min to completely dissolve the stearic acid and obtain the modifier.

[0041] (3) Place the rusted steel sheet (2×3cm) in the tannic acid aqueous solution prepared in step (1), stir with a glass rod, soak for 2 hours, take it out, wash with distilled water, remove excess tannic acid (TA) from the surface, and then dry with cold air.

[0042] (4) Adjust the pH of the tannic acid aqueous solution to 8 with 1 mol / L NaOH solution, then place the rusted steel sheet treated in step (3) into the tannic acid aqueous solution after pH adjustment, soak for 1 minute, take it out, rinse it with water several times, and dry it in a constant temperature oven at 60℃.

[0043] (5) Immerse the rusted steel sheet treated in step (4) in AgNO3 solution for 2 hours. The concentration of AgNO3 solution is 2 mg / ml. After immersion, remove the sheet, rinse it with water, and then dry it in a constant temperature oven at 60℃ to obtain rust-converted steel sheet.

[0044] This step allows for the construction of a well-defined micro / nano hierarchical structure, depositing reduced silver nanoparticles and aggregates onto the surface of the composite coating. The aggregates typically refer to substances generated during the reduction reaction, where silver nitrate ions (Ag+) are gradually reduced to elemental silver (Ag). These aggregates, along with organic compounds such as carbon-based and nitrogen-based compounds and surfactants, interact with the reduced silver particles, resulting in the aggregation of large particles or aggregates.

[0045] (6) Place the rust-converting steel sheet treated in step (5) into the modifier prepared in step (2) and react for 1 hour. After the reaction is complete, slowly remove it and place it in the air to dry naturally to obtain the modified superhydrophobic rust-converting steel sheet.

[0046] Example 2

[0047] A method for preparing a rust-converting waterproof coating includes the following steps:

[0048] (1) Add 2g of tannic acid (TA) to 1000ml of water and stir with a glass rod for 20min to completely dissolve it, so as to obtain an aqueous solution of tannic acid with a concentration of 2mg / ml.

[0049] (2) Stearic acid (SA) was added to anhydrous ethanol at a mass ratio of 1:40. Stirred with a magnetic stirrer at 65°C and 500r / min for 15min until it was completely dissolved to obtain the modifier.

[0050] (3) Place the rusted steel sheet (2×3cm) in the tannic acid aqueous solution prepared in step (1), stir with a glass rod, soak for 3 hours, take it out, wash with distilled water, remove excess tannic acid (TA) from the surface, and then dry with cold air.

[0051] (4) Adjust the pH of the tannic acid aqueous solution to 8.5 with 1.2 mol / L NaOH solution, then place the rusted steel sheet treated in step (3) into the tannic acid aqueous solution after pH adjustment, soak for 3 minutes, take it out, rinse it with water several times, and dry it in a constant temperature oven at 70℃.

[0052] (5) Immerse the rusted steel sheet treated in step (4) in AgNO3 solution for 3 hours. The concentration of AgNO3 solution is 3 mg / ml. After immersion, remove the sheet, rinse it with water, and then dry it in a constant temperature oven at 60℃ to obtain rust-converted steel sheet.

[0053] (6) Place the rust-converting steel sheet treated in step (5) into the modifier prepared in step (2) and react for 2 hours. After the reaction is complete, slowly remove it and place it in the air to dry naturally to obtain the modified superhydrophobic rust-converting steel sheet.

[0054] Example 3

[0055] A method for preparing a rust-converting waterproof coating includes the following steps:

[0056] (1) Add 4g of tannic acid (TA) to 1000ml of water and stir with a glass rod for 15min to completely dissolve it, so as to obtain an aqueous solution of tannic acid with a concentration of 4mg / ml.

[0057] (2) Stearic acid (SA) was added to anhydrous ethanol at a mass ratio of 1:60. The mixture was stirred with a magnetic stirrer at 60°C and 550r / min for 12 minutes to completely dissolve the stearic acid and obtain the modifier.

[0058] (3) Place the rusted steel sheet (2×3cm) in the tannic acid aqueous solution prepared in step (1), stir with a glass rod, soak for 2.5 hours, take it out, wash with distilled water, remove excess tannic acid (TA) from the surface, and then dry with cold air.

[0059] (4) Adjust the pH of the tannic acid aqueous solution to 8 with 1 mol / L NaOH solution, then place the rusted steel sheet treated in step (3) into the tannic acid aqueous solution after pH adjustment, soak for 2 minutes, take it out, rinse it with water several times, and dry it in a constant temperature oven at 65℃.

[0060] (5) Immerse the rusted steel sheet treated in step (4) in AgNO3 solution for 2.5 h. The concentration of AgNO3 solution is 2 mg / ml. After immersion, remove the sheet, rinse it with water, and then dry it in a constant temperature oven at 60℃ to obtain rust-converted steel sheet.

[0061] (6) Place the rust-converting steel sheet treated in step (5) into the modifier prepared in step (2) and react for 1.5 hours. After the reaction is completed, slowly remove it and place it in the air to dry naturally to obtain the modified superhydrophobic rust-converting steel sheet.

[0062] A schematic diagram illustrating the principle of this invention for preparing a superhydrophobic rust-converting coating is shown below. Figure 2 As shown. Figure 2 In the formula, 1 represents a piece of stainless steel, 2 represents tannic acid molecules, and 3 represents stearic acid. From... Figure 2 The construction of the superhydrophobic rust-converting coating of this invention can be clearly seen in the image.

[0063] The surface morphology of the untreated rusted steel sheet from Example 1 and the prepared superhydrophobic rust-converted steel sheet was observed by scanning electron microscopy (SEM). The wettability of the steel sheet was determined by measuring the water contact angle. Its chemical functional groups were observed by FT-IR. Its mechanical properties were demonstrated by sandpaper abrasion test and tape peeling test.

[0064] Figure 3 This is a surface morphology image of the rusted steel sheet before treatment in Embodiment 1 of the present invention. From... Figure 3As can be seen, the surface morphology of the rusted iron sheet exhibits fine-grained rust, a highly porous and rough structure, with many corrosion pits clearly visible. This indicates that the iron dissolves through pitting corrosion, forming a porous layer of corrosion products with cavities of varying sizes. Figure 4 This is a surface morphology image of the superhydrophobic rust-converting steel sheet prepared in Example 1 of the present invention. Figure 4 As can be seen, an amorphous, dense crack layer formed after the sample surface treatment. These changes indicate that the rust phase has been transformed by tannic acid, forming a dense and stable chelate that adheres stably to the substrate surface, demonstrating a significant rust transformation effect and a rough surface. Furthermore, the substrate surface exhibits a coral-like micro / nano structure. These rough surface structures can trap air, preventing direct contact with corrosive ions.

[0065] Figure 5 This is a water contact angle (WCA) test diagram of the rusted steel sheet before treatment in Embodiment 1 of the present invention. Figure 6 This is a test image of the surface water contact angle of the superhydrophobic rust-converting steel sheet prepared in Example 1 of the present invention. Figure 5 and Figure 6 It can be seen that the water contact angle (WCA) of the untreated rusted steel sheet surface is only 82.4 degrees, while the water contact angle (WCA) of the sample surface after rust modification reaches 152.6 degrees, indicating that the hydrophobic modification is successful and a superhydrophobic modified coating is obtained.

[0066] To further investigate the complexation effect between the surface of the rusted steel sheet and tannic acid molecules, infrared spectroscopy analysis was performed on the sample. Figure 7 As shown. The presence of -OH groups after impregnation with tannic acid (TA) indicates that the tannic acid is grafted onto the stainless steel surface via group grafting, rather than simple physical adsorption. Compared to the stainless steel surface, the impregnated surface at 2948 cm⁻¹... -1 The characteristic peak CH of TA was observed at the location. This indicates that the -OH group in the gallic acid group of TA is converted into an Fe-O bond, which can crosslink TA molecules to form a dense iron tannate coating. Furthermore, several characteristic peaks of aromatic compounds were observed in the surface spectrum after impregnation. These peaks correspond to the C=O group at a stretching depth of 1712 cm⁻¹. -1 The stretching length of C=C is 1627cm. -1 The deformation and tensile amount is 1219cm. -1 and 680cm -1 CH. Therefore, the results demonstrate that the formation of the protective coating and the adsorption of TA molecules were successful.

[0067] Two abrasion tests, sandpaper abrasion and 90° tape peel, were used to evaluate the durability of the superhydrophobic coating. Figure 8As shown, during the sandpaper abrasion process, the water contact angle remained almost unchanged within 40 cycles. After 40 cycles, the water contact angle decreased slightly, while the water slip angle increased slightly. The superhydrophobic coating maintained its superhydrophobicity until the 80th cycle. After 110 cycles of 90° tape peeling, the superhydrophobic coating still maintained its superhydrophobicity, demonstrating its good mechanical stability.

[0068] In summary, this invention utilizes the coordination and complexation of tannic acid with metal ions, eliminating the need for pre-rust removal. It transforms rust into a protective film, converting the complex rust composition into a stable product that prevents re-rusting in marine environments for extended periods. Furthermore, the superhydrophobic coating prepared by this invention exhibits uniform roughness, excellent hydrophobicity, good mechanical properties, and high stability, effectively resisting the entry of corrosive ions in the marine environment and significantly enhancing its corrosion resistance. Additionally, the tannic acid and stearic acid used in this invention are both environmentally friendly materials. The preparation process does not use volatile solvents, causing no pollution or harm to the environment or human health. Moreover, it requires no heating treatment, resulting in low preparation costs and facilitating large-scale industrial application.

Claims

1. A method for preparing a rust-converting waterproof coating, characterized in that... Includes the following steps: (1) Add tannic acid to water and stir to dissolve it to obtain an aqueous solution of tannic acid; (2) Stearic acid is added to anhydrous ethanol and stirred to dissolve, thus obtaining the modifier; (3) Soak the rusted sample in tannic acid aqueous solution for the first time. After soaking, take it out, wash it with water, and dry it with cold air. (4) Adjust the pH value of the tannic acid aqueous solution with NaOH solution, and then soak the rusted sample treated in step (3) in the tannic acid aqueous solution after adjusting the pH value for the second time. After soaking, take it out, wash it with water, and dry it in a constant temperature oven. (5) Immerse the rusted sample treated in step (4) in AgNO3 solution. After immersion, take it out, rinse it with water, and dry it in a constant temperature oven to obtain the rust-converted sample. (6) Place the rust conversion sample treated in step (5) into the modifier prepared in step (2) for reaction. After the reaction is completed, take it out and place it in the air to dry naturally to obtain the modified superhydrophobic rust conversion sample. In step (2): the mass ratio of stearic acid to anhydrous ethanol is 1:40-60; a magnetic stirrer is used for stirring, the stirring speed is controlled at 500-600 r / min, the stirring temperature is 60-65℃, and the stirring time is 10-15min; In step (4): the concentration of the NaOH solution is 1-1.2 mol / L, the pH value of the tannic acid aqueous solution is adjusted to 8-8.5 using NaOH solution; the second soaking time is controlled to be 1-3 min; the drying temperature of the constant temperature box is controlled to be 60-70℃; In step (5): the concentration of the AgNO3 solution is 2-3 mg / ml; the soaking time is controlled to be 2-3 h; and the drying temperature of the constant temperature box is 60-70 ℃.

2. The method for preparing a rust-converting waterproof coating according to claim 1, characterized in that, In step (1): the stirring time is controlled to be 15-20 min; the concentration of the tannic acid aqueous solution is 2-4 mg / ml.

3. The method for preparing a rust-converting waterproof coating according to claim 1, characterized in that, In step (3): the sample is stirred during soaking so that the rusty sample is suspended in the tannic acid aqueous solution; the first soaking time is controlled to be 2-3 hours.

4. The method for preparing a rust-converting waterproof coating according to claim 1, characterized in that, In step (6): the reaction time is 1-2 hours.

Citation Information

Patent Citations

  • Preparation method of super-hydrophobic sponge for adsorbing organic solvent

    CN108822332A

  • Superhydrophobic manganese dioxide coating on metallic material surface and preparation method thereof

    CN109666925A